2011
DOI: 10.1021/cg101504c
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a Single Primary Nucleation Event and Secondary Nucleation in Crystallization Processes

Abstract: The quality of a crystalline product is defined by its crystal size distribution, purity, morphology, and kind of solid state. It is highly influenced by the nucleation behavior during the crystallization process. A convenient and often used experimental method for determining nucleation behavior is by measuring metastable zone widths (MSZW) in relatively small volumes. However, to what extent these can be related to nucleation behavior on larger (industrial) scales is not known. Two major reasons for this are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
171
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(180 citation statements)
references
References 19 publications
5
171
3
1
Order By: Relevance
“…Visualization of the stirred solution in 3 ml volumes showed the presence of a large single crystal before a crystal suspension was detected by the decrease in the transmission of light through the sample [8]. Figure 3 shows a clear solution, the single parent crystal and the suspension after detection through a decrease in the 25 transmission of light.…”
Section: The Single Nucleus Mechanismmentioning
confidence: 98%
“…Visualization of the stirred solution in 3 ml volumes showed the presence of a large single crystal before a crystal suspension was detected by the decrease in the transmission of light through the sample [8]. Figure 3 shows a clear solution, the single parent crystal and the suspension after detection through a decrease in the 25 transmission of light.…”
Section: The Single Nucleus Mechanismmentioning
confidence: 98%
“…These two quantities are undoubtedly related to nucleation kinetics. The volume of sample solution used for the experimental determination of these values ranges from flask size of litters [2] down to droplet size of several hundred cubic micrometers [3]. Nucleation is stochastic in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kadam et al [2] reported MSZW data obtained for primary nucleation of paracetamol from stirred aqueous solution. The MSZW, obtained on a 1 mL sample, was not reproducible and distributed widely.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations